Stress, workload, time management and student performance - Ab. Hamid, Kamal; Abdul Rahman, Nor Irwani (School of Technology Management and Logistics (STML), 2019)
Education becomes one of major contribution to capital development in Malaysia. Education plays a great role in the life of everyone all through the life. Getting proper education is very necessary to get success and have a better life. Education develops personality of the people, provides physical and mental standard and transforms people’s living status. It promotes the feeling of physical, mental and social well-being by providing better life. Good quality education is constructive in nature which constructs the future. It helps a person to improve status of mind, body and spirit. However, the opportunity that have given to the community or workers for continue the study will affect to their daily routine, especially for those workers who done two different task at the same time. They need to be smart in order to balance their life, responsibility towards work and study. Otherwise, they will face a lot of issues when they failed to cope with their study due to working duration constrain. Equally important, their study performance also needs to be concern so do with their work performance. Realizing this solemn effect, this study attempts to examine the relationship between stresses workload and time management of part time student towards their performance in studies. The outlined objectives are: i. To identify relationship between stress towards part time student’s performance. ii. To identify relationship between workload towards part time student’s performance. iii. To identify relationship between time management towards part time student’s performance.